AN ANALYSIS OF DEIXIS IN SONG LYRICS ENTITLED “PERFECT” BY ED SHEERAN - Aulia, Ersa Anita (FKIP Universitas Samawa, 2023)
Enriching knowledge, especially in English can happen in other fields such as song, movie, poetry, novel, and many more. Currently, many people prefer to increase their vocabulary by using a song that consists of a combination of music and lyrics to definite a sensitivity of heart, idea, and the way of thinking. Through the lyric plus song music, the listener can express their idea, feeling, and emotion and learn. In this research, the researcher focuses to examine the use of deixis through the song lyrics of Perfect by Ed Sheeran. The researcher analyzed it is to figure out the kinds of deixis that occur in the song of Ed Sheeran. By using qualitative research, the researchers found some fascinating results. The researcher discovered that there were two types of deixis, such as the personal deixis, and the temporal deixis. In the personal deixis, the song consisted of first person (I, me, my, we, mine, our), second person (your, your), and third person (it, she, her). The last finding was temporal deixis that concentrated on defining the time (this time, in the dark, tonight, that someday, now). Additionally, this research was conducted to help further researchers to examine deixis which focused to display or underline which is used to represent those foundations in the expression which for directly to the situation.